PENGARUH SIKAP DAN PERILAKU TERHADAP KEBERADAAN SAMPAH PADA MASYARAKAT PESISIR DESA KILENSARI PANARUKAN SITUBONDO - Riska Ayu Pramesthi; Sriono Sriono (Growth, 2019)
Trash is part of something that is unused, slurred or something, and it's not useful. The consciousness of the individual to determine the real behavior and behavior that may be the case that's called attitude. The waste problem in Indonesia is a complicated issue, because of behavior-behavior communities that still less care to the environment itself. The purpose of this research is to know the influence of attitude and behavior towards the existence of trash in the coastal community of village Kilensari Panarukan Situbondo. Population data collected in the study are all the coastal communities South of the village Kilensari Panarukan totaling 210 inhabitants. The sample used totaled 68 inhabitants. The sampling technique used was purposive random sampling techniques with the determination of the total sample of respondents using the formula slovin. External research achieved i.e. contribute to the increase of progress of life economy in coastal communities. Provide knowledge and development the importance of attitude and approach in managing the associated behavior and create superior human resources. Increasing knowledge about the curriculum or courses that better mainly subjects related to organizational behavior